ANALISIS DAN PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM PADA SMA NEGERI 6 KOTA JAMBI - Suprapto, Cahyo Adi; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2017)
The goals of the thesis were to design a system that supports the documentation and dissemination of better knowledge to all educators and education personnel in SMAN 6 Kota Jambi. How to design a knowledge management system that can transfer knowledge from documents, guides and solutions of cases that have occurred so that it can be distributed to all teachers and educational personnel equally. Factors to be studied are the main components of Knowledge Management (KM) ie people, process, and technology and for the design of Knowledge Management System using knowledge roadmap theory from Tiwana. The data in this research is taken from interview with Headmaster, Teacher and IT Staff at SMAN 6 Kota Jambi. The tool used is Alfrsco Community Edition. With this research is expected to assist in documenting and disseminating knowledge in SMAN 6 Kota Jambi